If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 13 = 49 Reorder the terms: 13 + x = 49 Solving 13 + x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = 49 + -13 Combine like terms: 13 + -13 = 0 0 + x = 49 + -13 x = 49 + -13 Combine like terms: 49 + -13 = 36 x = 36 Simplifying x = 36
| x^2-7x+42=0 | | 9x^3y+81x^2y-90xy=0 | | 7p+3=-11 | | x+3x+x+3x=64 | | 4-2p=6 | | 8x-30+6x-21=10x-27+2x+9 | | P(x)=x^4+7x^3-50x^2+30x-24 | | -1(1+7x)-6(-7-1x)=36 | | x^4+3x^3+2x^2+30x=0 | | g+g+9=29 | | 3x^2-13x-56=0 | | 45xy^4-30xy^2z+5xz^2=0 | | 14-9=12+18 | | 73+6n=46 | | G+(g+9)=20 | | 5*x=120 | | 4z^2+18-27z=0 | | 8-5lnx=7 | | zg-15=13 | | 20a=19 | | 2f+f^2=440 | | 31-5k=14 | | 3*x=93 | | 72xy^4-24xy^2z+2xz^2=0 | | 2(3+3)+12= | | t=-16t^2+100t+155 | | 2(3)= | | 7x^2+56x-91=0 | | 2(3*4)-55(2)= | | 19k-34=23 | | 68=5x-2(-3x+10) | | 4x^2+29+30=0 |